Reproductive Biology of Hampala macrolepidota Kuhl &Van Hasselt, 1823 from the Kampar Kiri RiverMentulik VillageKampar Kiri Hilir District Kampar Regency Riau Province - Kartini, Tirta Amelia; Efizon, Deni; Efawani, Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Â ABSTRACTÂ Hampala macrolepidota is present in the Kampar Kiri River. A study aims to understand the reproductive biology ofH. macrolepidotahas been conducted from February to April 2018. Fish samplingswereconducted 4 times, one/ 2 weeks. Parameters measured were sex ratio, gonad maturity level, gonad somatic index (GSI), fecundity and egg diameter. Results shown that there were 42 males and10 females (sex ratio 4:1). Male has slimmer body, darker body color than those of the female. Size at maturity level in male ranged from 102-300 mm (SL) and 30-700 g BW,while that of the females was 173-330 mm (SL) and 150-990 g BW. The GSI of male ranged from0.04-2.75%, while that of the females was0.94-12.43%. The fecundity was 136.534 eggs/fish, and the egg diameter was 0.5-0.9 mm.Keywords: Sex ratio, gonad maturity level, gonad somatic index, fecundity